Fiscal policy in Poland from perspective of the EU member state - Danuta Gotz-Kozierkiewicz (Transformation, Integration and Globalization Economic Research (TIGER), 2004)
Fiscal policy in Poland faces challenges both in the view of the critical position of public finance in the recent years and the UE accession. The Polish economy performance in the Union, when assessed from the perspective of the participation in the euro area, requires not only the fulfilment of the nominal convergence criteria as expected but, first of all, the real convergence. Fiscal policy evolution in Poland should aim at its more intensive use in the stable economic growth management at the introductory stage, preceding the entry to the monetary union as well as, and even more, after becoming its member - in addition to common, supranational monetary policies. This evolution parallel to the accomplishment of the economy's transformation at the macro and micro level would also determine an optimal speed of the country's inclusion into the successive, ever more advanced forms of integration.
Keywords: 330; Finanzpolitik; EU-Mitgliedschaft; Polen